ANALISIS PENGARUH KECERDASAN EMOSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMA 2 PSKD MATRAMAN - Debora Meilany; Christina Natalia; Desideria Regina (Universitas Kristen Indonesia, 2026)
This study focuses on investigating the impact of emotions and discipline in the work environment on teacher performance at SMA 2 PSKD Matraman. Teaching performance is a very important aspect in improving the quality of education, which is influenced by teachers' ability to manage emotions and discipline while performing their duties. This study used quantitative methods, followed by multiple linear regression analysis. Data were collected from 30 teachers through the total sampling method. The findings show that emotional intelligence has a significant positive influence on teachers' performance, where individuals with high emotional intelligence are able to manage emotions well, build better relationships, and improve teaching quality. In addition, discipline contributes significantly to teacher performance. Those with high levels of discipline are usually more reliable, show up on time and complete tasks well. Overall, emotional intelligence and commitment to performance are interrelated and have a significant impact on improving teacher outcomes. This study also recommends that training programs in emotional intelligence be strengthened and a better discipline system be implemented to improve the quality of education at SMA 2 PSKD Matraman. Keywords: Emotional intelligence, Work discipline, Teacher performance, SMA 2 PSKD Matraman.